Child grippe epidemic in Lima 1918 - 1919 - Eyzaguirre, Rómulo (1920)
At the meeting of March 18, 1919, held by the Academy of Medicine of Paris, Professor CH. ACHARD said: "One of the peculiarities of the prevailing epidemic of grippe, noted the rarity of the disease in infants, and it was thought that the newborn enjoyed a certain immunity, however, we have observed in our little creche. Necker Hospital, 32 cases in children under two years until ", and then the distinguished professor of clinical medicine, the 32 cases in groups of clinical forms, from our present point of view, no intervention rates.